Adverse childhood experiences and their impact on primary headache patients: a cross-sectional study - Pabón Moreno, Alexander; Gonzalez Galindo, Valentina; Hurtado-Ortiz, Alexandra; Licht-Ardila, Maricel; Manrique-Hernández, Edgar Fabian; Mendoza-Monsalve, Alejandra; Pérez-Cárdenas, Angelica Tatiana; Forero, Ximena Jaely; Portilla, Andreina Judith; Silva Sieger, Federico; Llanez Anaya, Elkin (Frontiers in Psychiatry, 2025)
IntroductionAdverse Childhood Experiences (ACEs), including abuse and household dysfunction, can have lasting effects on development and health, increasing risks for chronic diseases and mental health issues.Objectiveto estimate the prevalence of ACEs in this population and to determine the factors associated with these experiences.MethodsA cross-sectional study was conducted at a Colombian high-complexity institution, including adults with primary headaches according to ICHD-3 criteria. Statistical analysis involved bivariate comparisons and multivariate logistic regression, with goodness-of-fit assessed using the Hosmer and Lemeshow test. All analyses were performed using Stata 16.Results138 patients with primary headaches were included, 77.54% reported experiencing some form of ACEs, with 34.06% having scores of 4 or higher. Physical abuse was the most common ACE (9.13%). Women had a higher probability of reporting ACEs (OR: 8.613, 95% CI: 1.006-73.776, p = 0.049). Those with severe disability (MIDAS score) were less likely to report severe ACEs (OR: 0.293, 95% CI: 0.096-0.899, p = 0.032).ConclusionThis study demonstrates a strong relationship between adverse childhood experiences and primary headaches, highlighting the need to incorporate childhood trauma assessment into neurological practice.